Development of Date Fruit (Phoenix dactylifera L.) Wine - Tandee, Kanokwan; Wanchana, Junjira; Rahong, Nunnapat; Choocherd, Rungarun; Chouypradit, Wannapa; Sumritsakun, Chaiyot; Kittiwachana, Sila; Mahatheeranon, Sugunya (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
Date fruit (Phoenix dactylifera L.), known for its sweetness and nutrition, has been used to develop a low-alcohol wine suitable for health-conscious individuals who enjoy socializing. Current study aimed to select an appropriate yeast strain and to determine optimal conditions such as initial total soluble solids and pH for producing a healthy and appealing date fruit wine. Among seven strains of Saccharomyces cerevisiae examined (71B, BM4x4, ICV-D47, EC-1118, K1-V1116, QA23, RC212), strain K1-V1116 was found to produce a wine with lower pH and alcohol content, higher acidity, total phenolic content, and ferric reducing ability power. Date fruit wine made with strain K1-V1116 also received the highest scores for flavor and overall liking. Further experiments were conducted using date fruit juice with three levels of different initial total soluble solids (5 %, 10 %, and 15 %). The results indicated that 15 % initial total soluble solids produced wine with superior characteristics in terms of total soluble solids, pH, acidity, alcohol content, reducing sugar content, total phenolic content, ABTS radical cation decolorization, ferric reducing ability power compared to lower concentrations. Date fruit wine produced with 15 % initial total soluble solids also received the highest scores for color and overall liking. Additionally, the date fruit juice with 15 % initial total soluble solids was used to produce wine at three levels of pH value (4.0, 4.5, 5.0) and wines produced at pH 4.5 were rated the highest for flavor and overall liking. In conclusion, using S. cerevisiae K1-V1116 to ferment date fruit juice with 15 % initial total solids at pH 4.5 can yield a well-liked, low-alcohol wine.